Carbohydrate attenuates perceived exertion during intermittent exercise and recovery - Utter, A. C.; Kang, J.; Niemann, D. C.; Dumke, C. L.; McAnulty, S. R.; McAnulty, L. S. (Medicine & Science in Sports & Exercise, 2007)
Purpose: The purpose of this study was to examine the effect of carbohydrate supplementation on differentiated and undifferentiated ratings of perceived exertion (RPE) during prolonged intermittent exercise and recovery.